PARTICIPATION OF WOMEN IN AGRICULTURE IN RANGIA AND KAMALPUR BLOCK OF KAMRUP DISTRICT OF ASSAM- AN ECONOMIC ANALYSIS - Sarma, Pallavi; Goswami, Debotpal (International Journal of Research -GRANTHAALAYAH, 2022)
Women play a significant role in agriculture and allied operations. Besides looking after the family and performing all shorts of household activities, women are actively busy from dawn to dusk in various agricultural operations. A few studies have been made on this regard in India as well as in the state basically in Assam. In order to carry out the study, a district of Assam, named Kamrup is selected as the sample district because of the availability of female agricultural labourer. Keeping in view these facts, the present study has been designed to explore the extent of female participation in agriculture and their contribution to total household income.